Exploring the Wage Gap in the Republic of Moldova: A Vital Issue of Elderly System - Mariana Robu (Ovidius University Annals: Economic Sciences Series, 2023)
Gender wage gap remains a crucial issue in many countries around the world, including the Republic of Moldova. The purpose of this article is to explore the wage gap and its impact on the elderly population. The research aims to identify the factors that contribute to the wage gap and assess the extent to which the wage gap affects the economic security and well-being of the elderly population. We will analyze the policies and interventions that have been implemented in other countries to address the wage gap and identify good practices to recommend potential strategies that can be adopted in the Republic of Moldova. This paper represents a comprehensive synthesis of existing literature examining the wage gap and its impact on the elderly population. By analyzing areas of research that have been more fully explored and those that require further investigation, this study suggests avenues for future research.